Dinamika Motivasi Belajar Siswa: Tantangan dan Tren Baru dalam Era Teknologi dan Keterlibatan Komunitas - Marlina, Jenni; Mulyanti, Dety; Haru, Emanuel (STIPAS St. Sirilus Ruteng, 2024)
This article discusses the dynamics of student learning motivation: challenges and New Trends in the era of technology and community engagement. Student learning motivation is a crucial element in the world of education, which serves as the driving energy that drives students to act, pursue learning goals, and survive in the face of difficulties. In today's technological age, there are new challenges to student learning motivation. Advances in information technology have revolutionized the way students access information and learn, which may affect their motivation levels. Moreover, community involvement plays an increasingly significant role in the modern age of education. Given its complexity, it is important for educators to develop an in-depth understanding of effective ways to leverage technology and community involvement in increasing student learning motivation. The importance of understanding students' learning motivations in a technological context and community engagement has become a growing research topic, showing that this dynamic is highly relevant in today's educational practice. Therefore, through this background, the author invites readers to dive deeper into the factors that influence student learning motivation as well as ways to optimize the potential of technology and communities to form a supportive and motivating educational ecosystem.